1993
DOI: 10.1172/jci116801
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide (LPS) recognition in macrophages. Participation of LPS-binding protein and CD14 in LPS-induced adaptation in rabbit peritoneal exudate macrophages.

Abstract: Exposure of rabbit peritoneal exudate macrophages (PEM) or whole blood to picomolar concentrations ofLPS induces adaptation or hyporesponsiveness to LPS. Because of the importance of plasma LPS-binding protein (LBP) and the macrophage cell membrane protein CD14 in recognition of LPS, we examined the effect of LBP on LPS-induced adaptation in PEM. PEM exposed to LPS in the presence of LBP for 8 h were markedly less responsive to subsequent stimulation by LPS than monocytes/macrophages (M+) adapted in the absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…8 -10 The present study confirmed that adhesion and extravasation are in full progress at 6 hours and that most PMNs have disappeared by day 3, as indicated by the small and variable numbers of CD14-immunoreactive cells in the intima and media. Even though the CD14 stain does not distinguish between monocytes and PMNs, 23 very few monocytes enter the collared artery, 8 unless lipoproteins are infused into the collar. 24 To investigate the functional significance of PMN infiltration, the number of circulating PMNs was raised by continuous treatment with G-CSF, starting 3 days before collaring.…”
Section: Discussionmentioning
confidence: 99%
“…8 -10 The present study confirmed that adhesion and extravasation are in full progress at 6 hours and that most PMNs have disappeared by day 3, as indicated by the small and variable numbers of CD14-immunoreactive cells in the intima and media. Even though the CD14 stain does not distinguish between monocytes and PMNs, 23 very few monocytes enter the collared artery, 8 unless lipoproteins are infused into the collar. 24 To investigate the functional significance of PMN infiltration, the number of circulating PMNs was raised by continuous treatment with G-CSF, starting 3 days before collaring.…”
Section: Discussionmentioning
confidence: 99%
“…Likely mechanisms for the reduced responsiveness of these macrophages to LPS include defective recognition of LPS or deficiency in LPS-specific signal transduction pathways. This phenomenon was only exhibited when the cells where tolerized in the absence of LBP (Mathison et al 1993) which is an unlikely scenario in vivo.…”
Section: Lipopolysaccharide-binding Protein (Lbp) Lps-binding Proteimentioning
confidence: 97%
“…Increased expression of mCD14 (Ziegler-Heitbrock et al 1994) and sCD14 (Labeta et al 1993) is associated with the development of ET and has been described in animals and humans. Other models reported no change in mCD14 expression in humans, rabbits and mice (Mathison et al 1993;McCall et al 1993;Ziegler-Heitbrock et al 1997). In 2003, Heagy et al reported that mCD14 is not involved in the development of ET in human monocytes (Heagy et al 2003).…”
Section: Lbp and Cd14mentioning
confidence: 99%
See 1 more Smart Citation
“…The identity of the LPS-recognition complex has been recently established. It is believed to be composed of TLR4 [1], the main transducer of signals from LPS, the GPI-linked receptor CD14 [2] and a small exteriorized adaptor known as MD-2 [3]. All three molecules are believed to form a stable complex during LPS signaling and, based on germ-line targeting [4][5][6], each is indispensable for LPS responses.…”
Section: Introductionmentioning
confidence: 99%